2006
DOI: 10.1148/radiol.2412051185
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Stage I Lung Cancer Growth Rates Determined with Serial Volumetric CT Measurements

Abstract: At serial volumetric CT measurements, there was wide variability in growth rates. Some biopsy-proved cancers decreased in volume between examinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
65
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 27 publications
3
65
2
Order By: Relevance
“…The fact that lung cancers may become smaller prior to treatment has been reported, 7,9 and in our study, four lung cancers became smaller. The fact that cancers have been documented to decreased in size at some point in their development should 800 900 1,000 1,100 1,200 1,300 1,400 1,500 1,600 1,700 Volume ( have raised questions previously about the utility of equations that assume the exponential growth of lung cancers in order to determine whether a nodule is benign or malignant.…”
Section: Discussionsupporting
confidence: 72%
“…The fact that lung cancers may become smaller prior to treatment has been reported, 7,9 and in our study, four lung cancers became smaller. The fact that cancers have been documented to decreased in size at some point in their development should 800 900 1,000 1,100 1,200 1,300 1,400 1,500 1,600 1,700 Volume ( have raised questions previously about the utility of equations that assume the exponential growth of lung cancers in order to determine whether a nodule is benign or malignant.…”
Section: Discussionsupporting
confidence: 72%
“…Other studies have looked at DTs in lung cancer (6)(7)(8)(9)(10). Several studies have compared DT in squamous cell carcinoma (SCC) and AC, showing significantly shorter DT in SCC than in AC (6-8).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported DTs of untreated lung cancers of between 90 and 207 days. 6,11,21 More recently, Eastham and colleagues compared serial FDG-PET scans (not PET/CT) for 11 patients with NSCLC, and reported tumor volume DTs of 6.5 weeks (45 days) in 4 patients. 2 Experimental solid tumors often show early exponential initial growth with later slowing as they enlarge (Gompertzian growth pattern).…”
Section: Discussionmentioning
confidence: 99%